DotU expression is highly induced during in vivo infection and responsible for virulence and Hcp1 secretion in avian pathogenic Escherichia coli - Wang, Shaohui; Dai, Jianjun; Meng, Qingmei; Han, Xiangan; Han, Yue; Zhao, Yichao; Yang, Denghui; Ding, Chan; Yu, Shengqing (Frontiers in Microbiology, 2014)
Type VI secretion systems (T6SSs) contribute to pathogenicity in many pathogenic bacteria. Three distinguishable T6SS loci have been discovered in avian pathogenic Escherichia coli (APEC). The sequence of APEC T6SS2 locus is highly similar to the sequence of the newborn meningitis E. coli (NMEC) RS218 T6SS locus, which might contribute to meningitis pathogenesis. However, little is known about the function of APEC T6SS2. We showed that the APEC T6SS2 component organelle trafficking protein (DotU) could elicit antibodies in infected ducks, suggesting that DotU might be involved in APEC pathogenicity. To investigate DotU in APEC pathogenesis, mutant and complemented strains were constructed and characterized. Inactivation of the APEC dotU gene attenuated virulence in ducks, diminished resistance to normal duck serum, and reduced survival in macrophage cells and ducks. Furthermore, deletion of the dotU gene abolished hemolysin-coregulated protein (Hcp) 1 secretion, leading to decreased interleukin (IL)-6 and IL-8 gene expression in HD-11 chicken macrophages. These functions were restored for the complementation strain. Our results demonstrated that DotU plays key roles in the APEC pathogenesis, Hcp1 secretion and intracellular host response modulation.